2015
DOI: 10.1590/0104-1428.1961
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystallization of poly(3-hydroxybutyrate): effect of heating/cooling rates on phase transformation

Abstract: SbstractWe studied the crystallization and melting phenomena of poly (3-hydroxybutyrate) (PHB), a biodegradable and biocompatible semi-crystalline thermoplastic, obtained from renewable resources. Its high crystallinity motivated several studies on crystallization and melting behavior, and also on ways to increase the amorphous polymer fraction. The effect of heating and cooling rates on the crystallization and melting of commercial PHB was investigated by differential scanning calorimetry. Several rates, rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
0
19
0
5
Order By: Relevance
“…Some studies have indicated this multiple melting behavior of PHB is contributted to different crystalline structure in PHB during DSC melting scan [47][48][49] . Hong et al 49 refer to the smaller peak as a melting temperature of small and imperfect crystallites that formed during evaporation of the solvent.…”
Section: Dsc Of the Fibers And Polymeric Matrixmentioning
confidence: 99%
“…Some studies have indicated this multiple melting behavior of PHB is contributted to different crystalline structure in PHB during DSC melting scan [47][48][49] . Hong et al 49 refer to the smaller peak as a melting temperature of small and imperfect crystallites that formed during evaporation of the solvent.…”
Section: Dsc Of the Fibers And Polymeric Matrixmentioning
confidence: 99%
“…Thus, studies of processing conditions and the crystallization process are necessary for understanding and controlling the properties of the final product. Researches are being conducted with the objective to optimize those conditions [6][7][8][9][10]; there are previous works with neat PHB, PHB/PS blends, PHB/carbon black and PHB/babassu composites, the improvement of PHB properties, the increase in thermal stability upon addition of carbon black, decrease in crystallinity degree with PS addition, rational crystallization control through applying defined heating/cooling DSC rates were reached in our works [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 91%
“…The disadvantages related to its oversized spherulites, such as brittleness and mechanical performance loss, can be avoided by the introduction of fillers and inorganic additives, which improve toughness and electrical and magnetic properties [12]. Investigations were realized about the usage of PHB in many compounds, such as PHB/talc, PHB/polyethylene terephthalate (PET), PHB/polyamide 11 (PA 11), PHB/carbon black, and it was observed a faster crystallization from the molten [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study of crystallization and melting behavior is basic to understand and control of material properties and processing necessary to get them. An experiment was developed in order to understand the effect of the thermal cycles in the polymer phase transition suggesting that the crystallinity of PHB can be controlled by the thermal cycles of heating and cooling to which the material is subjected [82].…”
Section: Aging and Mechanical Characteristicsmentioning
confidence: 99%